2007
DOI: 10.1097/01.tp.0000250478.00567.e5
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Human Natural Antibodies to Endothelial Cells From Gal??(1,3)Gal-Deficient Pigs

Abstract: The generation of Gal-deficient pigs has overcome hyperacute anti-Gal-mediated xenograft rejection in nonhuman primates. Non-Gal anti-porcine NAb represent a potentially relevant immunological hurdle in a subgroup of individuals by inducing endothelial damage in xenografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 40 publications
2
73
0
Order By: Relevance
“…Other endogenous factors, including MD-2 and the lipoprotein receptor, may be required for interaction with TLR4 (18,25). We have reported that the sulfated polysaccharide carrageenan, which has the unusual ␣-1,3-galactosidic link that is the epitope for the anti-Gal antibody (2,12), is recognized by TLR4 and induces an innate immune response mediated by Bcl10, as well as an ROS-mediated inflammatory response (3,4). The O-antigen of enteropathogenic Escherichia coli O86 and O127 appears to have some similarly configured linkages between galactose and N-acetylgalactosamine residues (10), suggesting a possible relationship to pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Other endogenous factors, including MD-2 and the lipoprotein receptor, may be required for interaction with TLR4 (18,25). We have reported that the sulfated polysaccharide carrageenan, which has the unusual ␣-1,3-galactosidic link that is the epitope for the anti-Gal antibody (2,12), is recognized by TLR4 and induces an innate immune response mediated by Bcl10, as well as an ROS-mediated inflammatory response (3,4). The O-antigen of enteropathogenic Escherichia coli O86 and O127 appears to have some similarly configured linkages between galactose and N-acetylgalactosamine residues (10), suggesting a possible relationship to pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…The latter contributes to the confusion about the role of IgG (subclasses) versus IgM Abs in humoral rejection. To resolve these problems, we utilized a recently established semiquantitative flow cytometry-based method, ABO fluorescence-activated cell sorting (ABO-FACS), to measure anti-A/B and antiporcine IgM/IgG Ab serum levels prior to, and after, a living-donor ABO-incompatible kidney transplantation (14,15).…”
mentioning
confidence: 99%
“…The biological reactivity of CGN may be attributable to some extent to its activation of a pathway of innate immunity, due to CGN's unique structure that includes the immunogenic gal(α-1,3)gal epitope [1,2]. Of mammals, only humans and Old World apes lack the alpha-1,3-galactosyl transferase enzyme that is required to form the alpha-1,3-galactosidic linkage, recognized by the anti-Gal antibody [3,4].…”
Section: Introductionmentioning
confidence: 99%